An ethnobotanical study of wild edible plants used by the Tibetan in the Rongjia River Valley, Tibet, China - Jin Wang; Xiaoyong Ding; Chang-An Guo; Xiong Zhang; Haowen Feng; Huizhao Yang; Yuhua Wang (BMC, 2023)
Abstract Background Wild edible plants (WEPs) play a crucial role in communities with limited communication with the outside world, where unstable factors, such as poor food supply and insufficient access to timely nutritional supplementation, are common, as in the Himalayan region. To document the traditional knowledge of WEPs and explore their significance for communities with minimal global economic exchange, an ethnobotanical study was conducted in the town of Rongjia, which lies in a narrow valley near Mount Everest, Tibet, China. Methods This ethnobotanical study was conducted in three villages in the Rongjia River Valley between August 2021 and June 2023. Semi-structured interviews and participatory observations were used to collect information on WEPs. The fieldwork was performed with the assistance of local guides. Voucher specimens were collected from each documented plant species for taxonomic identification. We used the use report (UR) and relative frequency of citations (RFC) to evaluate the comprehensive utilization value of WEPs. Results We interviewed 161 informants who provided us with 2499 use reports. We collected 50 WEPs belonging to 28 families and 42 genera used by the Tibetan people in the Rongjia River Valley. WEPs are used in vegetables, fruits, seasonings, healthcare foods, substitute grains, and beverages. Wild vegetables were the most commonly used, followed by wild fruits. Leaves were the most commonly consumed part of the plant. The three most important WEPs ordered by RFC values were Rosa sericea var. glandulosa Osmaston (RFC = 0.76), Zanthoxylum bungeanum Maxim. (RFC = 0.75), and Urtica hyperborea Jacquem. ex Wedd. (RFC = 0.71). Other than that, we also document some of WEPs used in the past. Arisaema erubescens Schott, Pinellia ternata (Thunb.) Makino, and Satyrium nepalense var. ciliatum (Lindl.) Hook. f. used to serve as important substitute grains, are no longer in use, however, they remain vivid in the memories of older people. Conclusions WEPs included wild vegetables, fruits, seasonings, healthcare food, and substitute grains for Tibetan people in the Rongjia River Valley. Some WEPs have become important cultural symbols for older people, which can help in understanding the relationship between plants and local people in the past. In addition, WEPs can increase the resilience of local people living in remote areas when facing sudden destabilizing events in future. This is the significance of WEPs for communities with minimal global economic exchange. Therefore, we suggest that future studies focus more on WEPs in communities with limited communication with the world to improve their resilience.